Building a Comprehensive Content Management System with NPM, Vue.js, Node.js, Postgresql, and Strap - nashri aziz alhazmy; zahran nurafi chandra; pradana atmadiputra; yudi triyana (Liaison Journal of Engineering, 2023)
This article presents a content management system built using NPM v6.14.17, Vue.js v3.x, Node.js v14.20.1, Postgresql v13.2.1, and Strapi v3.6.6. The system provides various functionalities such as an Ongoing request and assessment dashboard, courier request management, meeting room booking, stationery management, tools request management, and transportation request management. Users can create requests for different categories and the admin can approve or reject requests. Additionally, the system allows users to generate reports on stock flow, courier activities, and driver assessment. The Master Data section enables users to view, search, and perform CRUD operations. The system offers a comprehensive solution for efficient content management. Keywords: content management system, NPM, Vue.js, Node.js, Postgresql, Strapi, dashboard, request management, admin approval, report generation, master data, CRUD operations.